Principles and Criteria of Phytocenotic Diversity Conservation (Through the Example of European Countries and Russia) - Lysenko, T M; Ivanova, A V; Kostina, N V; Davidenko, T N; Vasiukov, V M; Davidenko, O N; Nevskii, S A; Beliachenko, A A (KnE Life Sciences, 2019)
The article presents the review of currently existing views on the problem of phytocoenotic diversity protection in European countries and Russia. The principles and criteria for the identification of rare plant communities in need of protection, used by scientists from different countries are described. The authors had defined already published works of a monographic nature and projects, containing the information on the phytocenotic diversity of Europe in need of protection, and Green Books, published in the Russian Federation. Special attention is paid to the determination process of plant communities. It is noted that nowadays there is no single concept for the creation of Green Books. The phytocenosis protection inventories created in European countries that have a legislative basis, the Russian Green Books include vegetation monitoring data and have no legal basis.